Body Physics Motion to Metabolism - Davis, Lawrence (Open textbook library., 2018)
Body Physics sticks to the basic functioning of the human body, from motion to metabolism, as a common theme through which fundamental physics topics are introduced. Related practice, reinforcement and Lab activities are included. See the front matter for more details. Additional supplementary material, activities, and information can be found at: https://openoregon.pressbooks.pub/bpsupmat/